Hạn hán ở Đồng bằng Sông Hồng và một số giải pháp phòng chống - Dung, Nguyễn Thị Kim; Lưu, Đào Kim (Vietnam Journal of Earth Sciences, 2012)
SUMMARYThe drought of Red River Delta and mitigating solutionsFrom 2003 to recent, drought has been occurring widely in Red River Delta. Decreasing of flow of main river system, climate change and the operation unproperly of the upper reservoirs had led to water shortageof the downstream. In addition, increasing of water demand, degradation of water quality, and drought crisis management had made drought become more severely. The article focus on evaluating currentstatus, the main reason for the drought of Red River Delta and propose some solution for preventing and reducing consequences of drought, focusing problems as followed :- Water resources integrated management : integrated exploiting plan, distribution properly, and protection of water resources.- Engineering non-engineering solutions : building multi-purpose constructions at the upstream, applying water-saving irrigation method, seasonal cropshifting, building early warning system, as well as drought management.